The FTA Geoportal Manual - CGIAR Research Program on Forests, Trees and Agroforestry; Lokahita (CGIAR Research Program on Forests, Trees and Agroforestry, 2021)
As a collaborative research project, involving numerous researchers from member organisations, data sharing is important for FTA to optimise the use of their data inventory as well as for exchanging their knowledge, thus improving the quality and exposure of FTA research. This geoportal has been designed and developed as a system that can facilitate effective and efficient (geospatial) data access to, and data sharing among, FTA members’ internal data inventory as well as that of other organisations. Moreover, this geoportal is also expected to fulfil the need for showcasing or disseminating FTA’s research to a wider community/audience.